High prevalence of genotype 6 hepatitis C virus infection in Southern Taiwan using Abbott genotype assays - Jyh-Jou Chen; Hung-Da Tung; Pei-Lun Lee; Hsing-Tao Kuo; Ming-Jen Sheu; Chun-Ta Cheng; Tang-Wei Chuang; Hsu-Ju Kao; Na-Mi Lu; Li-Ching Wu; Chuan Lee (Journal of the Formosan Medical Association, 2020)
Background/Purpose: Abbott RealTime Genotype II assay can effectively identify hepatitis C virus (HCV) genotypes (GTs), but some GT 6 subtypes might not be differentiated from GT 1. Abbott RealTime Genotype II PLUS and sequencing might be needed to resolve these ambiguous results. Unlike the high prevalence of GT 6 in Southeast Asia, GT 6 had rarely been reported in Taiwan except in intravenous drug abusers (IDU). But the prevalence of GT 6 in Taiwan might be underestimated. We conducted this study to determine the GTs in a HCV endemic area in Southern Taiwan. Methods: A total of 1147 patients with hepatitis C viremia for direct acting antivirals (DAA) treatment at the Chi Mei medical system in Tainan were enrolled. Genotype was determined using a working flow consisted of Abbott GT II, PLUS assays and 5′ untranslated region (5′ UTR)/core sequencing. Results: Among the 1147 patients, 883 (77.0%) obtained GT results by GT II, 264 (23.0%) samples with ambiguous results by GT II assay received further tests, including 194 (73.5%) with PLUS assay and 70 (26.5%) with 5′UTR/core sequencing. Nearly three-quarters (73.5%) of ambiguous results by GT II assay were GT 6. Overall, 18.3% of samples were GT 6. Phylogenetic study of 11 samples of GT 6 subtypes showed 7 (63.6%) were 6 g. Conclusion: GT 6 is the major factor for high ambiguous rate by GT II. Unexpected high prevalence of GT 6 (18.3%) in Southern Taiwan, especially subtype 6 g, closely related to Indonesian strains, is first reported. Keywords: Genotype 6, Hepatitis C, Genotype assay, Direct acting antiviral